PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN KOMPETENSI TERHADAP KINERJA KARYAWAN BAGIAN TEKNISI PESAWAT PT. LION MENTARI AIRLINES - Imhar; Moch.Andyka Febrianto (Jurnal Publikasi Manajemen Informatika, 2022)
This study aims to determine and analyze the influence of the variables of leadership, organizational culture and competence on employee performance. The object of this research is PT. Lion Mentari Airlines which is one of the private airlines in Indonesia. The sample used in the study was 98 aircraft technician employees using a non-probability sampling technique with purposive sampling. Where questionnaires are distributed directly to aircraft technician employees who are permanent employees. Based on the results of the correlation test (R), the Coefficient Correlation (r) number is 0.458, which means that leadership (X1), organizational culture (X2), competence (X3) together have a moderate and positive relationship to employee performance (Y). . Furthermore, based on the significance value of F of 0.000, it is smaller than 0.05. The results of the F test which were analyzed using the SPSS program obtained a calculated F value of 8.311 with a significance of 0.000 <0.05, it can be concluded that the tested group had a significant (significant) difference. This result means that simultaneously there is a significant influence between leadership (X1), organizational culture (X2), competence (X3) on employee performance (Y).